Studi Literature Studi Literatur: Pengaruh Media Sosial Terhadap Kesehatan Mental Pada Remaja - Anggita Robbawahida Fatoni; Tristiadi Ardi Ardani (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study aims to understand how social media affects adolescents’ mental health. Today, social media has become an important part of adolescents’ daily lives, serving as a means of communication, entertainment, and self-expression. However, excessive use of social media can lead to various psychological problems such as stress, anxiety, and depression. This research uses the Systematic Literature Review (SLR) method by examining several journal articles that discuss the relationship between social media use and adolescents’ mental health. From 35 articles found, only 5 journals met the inclusion criteria and were analyzed further. The results show that the influence of social media on mental health is twofold. Wise use of social media can help adolescents gain social support and increase self-confidence, while excessive use tends to decrease psychological well-being. Factors such as self-control, family support, and social environment also affect the impact experienced by adolescents. Therefore, it is important for adolescents to learn how to use social media in a balanced and responsible way to prevent negative effects on their mental health.